Analysis of axial deformation in columns of a rural housing prototype built with bamboo in Bagua Chica, Peru - Cuadros, Emerson (2023)
The UN Sustainable Development Goal 11 promotes the construction of resilient infrastructures. In this sense, the Amazon region is a producer of bamboo, which presents an opportunity to develop the use of this plant and achieve this goal, which is why this research has explored the mechanical properties of bamboo, for this purpose a prototype of a full-scale rural house has been designed and built to evaluate the axial behavior of the columns of this building against an additional permanent load of 0.40 kN/m. It has also been monitored with a mixed system: for temperature and humidity it has been used low cost calibrated sensors mounted on an open source electronic prototyping system that, through an embedded Wifi connection allowed sending the measurements to a database in the cloud; on the other hand, for displacement control it has been used calibrated mechanical comparators, their measurements were performed through a wireless video system. The results indicate that a maximum deformation of Ɛ= 8x10-5 has been reached and that the columns are still at 1.6% of the elastic limit which indicates a good performance and a high safety factor.